Pengaruh Bystander Effect, Whistleblowing, Locus of Control Eksternal dan Moralitas Individu terhadap Terjadinya Kecurangan Laporan Keuangan - Hayatun Nufus; Nayang Helmayunita (Universitas Negeri Padang, 2023)
This study aims to analyze the effect of the bystander effect, whistleblowing, external locus of control and individual morality on the occurrence of financial statement fraud. This research is a quantitative research. The number of samples was determined using the slovin formula. The samples in this study were undergraduate accounting students class of 2018 at Universitas Negeri Padang, Universitas Andalas, Universitas Putra Indonesia and Universitas Bung Hatta. The data collection method used a questionnaire distributed through google form. The hypothesis in this study was tasted using multiple linear regression analysis with IBM SPSS 25. The results show that bystander effect has a significant effect on the occurrence financial statement fraud. Meanwhile, whistleblowing, external locus of control and individual morality have no effect on the occurrence of financial statement fraud.